The literary representation of the non-human: An ecocritical approach to Yere düşen dualar and Yeryüzü halleri - Hamzaçebi, Ezgi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
In the days of alarming ecological crisis, where does literature stand in the struggle while the other disciplines take actions in various ways? Can we talk about a literary text which is “ecologically sensitive”? What kind of features should such a text have ideally? In this thesis, focusing on the similarities and differences between Yere Düşen Dualar by Sema Kaygusuz and Yeryüzü Halleri by Birhan Keskin, I discuss the characteristics through which we can evaluate the ecological sensitivity of a literary text. I show that the aesthetic spaces of these texts are built with a language which focuses on bodily sensations and affects by moving away from the logocentric point of view, with the purpose of making the reader feel that all beings are fellow creatures by having bodies and finitude. With such an approach toward language, I claim that these texts go beyond humanism’s anthropocentric perspective and represent ethics of posthumanism. However, I also focus on some examples from the texts where the non-human is represented in different ways, and thus I discuss how ecological sensitivity and ethics of posthumanism can have various faces. Since there are not many studies related to this area in the departments of Turkish Literature, I aim to give an idea about certain topics within the area to those who have an interest in it. I also hope to contribute to Ecocriticism and Animal Studies by pointing out the peculiar ethical and aesthetic aspects of these texts.